On the Cryptobiina of the Arabian peninsula (Coleoptera: Staphylinidae: Paederinae) - Assing, Volker (Zootaxa, 2008)
The species of the paederine subtribe Cryptobiina from Oman and Yemen are examined. The following taxa are (re-) described and illustrated: Cryptomanum gen. n., C. omanicum (Coiffait, 1981), comb. n., C. spinosissimum sp. n. (Oman), and Afrobium arabicum sp. n. (Yemen, Iran). Keys to the genera of Cryptobiina present in the Western Palaearctic region and to the Cryptobiina species recorded from the south of the Arabian peninsula are provided.